A new mitochondrial probe combining pyrene and a triphenylphosphonium salt for cellular oxygen and free radical detection via fluorescence lifetime measurements. (3rd April 2022) - Wawi, Mohamad Jamal; Mahler, Christoph; Inguimbert, Nicolas; Marder, Todd B.; Ribou, Anne-Cécile
Abstract: To improve and diversify the quantification of reactive oxygen species (ROS) in mitochondria of single cells, we connected pyrene derivatives (PB) to a triphenylphosphonium salt (TPP + ) as a mitochondrial vector forming PB-TPP + probes. Two pyrene isomers with the n -butyltriphenylphosphonium moieties attached at their 1- or 2- positions were synthesized and characterized. Using the long fluorescence lifetime of pyrene, it was possible to monitor the variation of cellular free radicals and oxygen and to follow the reversibility of both quenchers in real-time. We compared the behavior of these new probes to the previously published pyrene-probes, functionalized by a mitochondrial-penetrating peptide, allowing their transfer to the mitochondria (Mito-PB) or to the cytosolic membrane for pyrene butyric acid (PBA). The high cellular uptake of the new probes allows cells to be loaded with an initial concentration 40 times lower than that for Mito-PB probes, without inducing perturbations in cell growth. The variation in free radicals and oxygen levels was monitored within cells under different stress conditions through the fluorescence lifetime of the new TPP + -based probes giving comparable results to those obtained for MPP-based probes. However, at a loading concentration as low as 25 nM, our technique allows the detection of increased production of free radicals in the mitochondria in the presence of the TPP + vector, a warning to the user of this well-known vector.